Determine of chemical elements and major ions in rain and pond water from Nanyang Technological University, Singapore - Fan, Xiao Xia (2010)
A university site was selected to determine trace element level and the major inorganic ions level in rain sample and pond sample. Total 30 samples for rain water and 36 samples for pond water were tested during December to March. Major ions were measured by ion chromatography and trace elements were measured by inductively coupled plasma - optical emission spectrometry. Mean pH value for rain water is 4.54. The source of acidic rain is (NO3)- and (SO4)2-. Precursor of these anions is from petro chemistry. Ions in pond sample went with rain sample. Also the trend of trace elements in pond samples is similar with rain sample. By factor analyzing, the pollution of both samples have same source.